Risk assessment of dietary exposure to pesticide residues in commercially available fruits and vegetables in Wenzhou， Zhejiang Province from 2020 to 2023 - HU Ning’en; LI Xiaodong; LI Ruifen; ZHANG Xiaoyi; CAI Yuanyuan; ZHENG Sanyan (Shanghai yufang yixue)
ObjectiveTo investigate the status and dietary intake risk of pesticide residues in fruits and vegetables sold in Wenzhou, Zhejiang Province from 2020 to 2023, so as to provide a scientific basis for the regulation and management of pesticide in the future.MethodsIn accordance with the requirements and methods specified in the “National Food Contamination and Hazardous Factor Risk Monitoring Work Manual” and the current corresponding national food inspection standards for various foods, a total of 807 samples of vegetables and fruits from various counties and districts of Wenzhou City were collected for testing and analysis. Eventually, 23 types of pesticides with a detection rate greater than 5% and those exceeding the standard were selected for dietary intake risk assessment.ResultsFrom 2020 to 2023, the overall detection rate of pesticide residues in fruits and vegetables monitored in Wenzhou was 71.62%, with an overall exceedance rate of 5.27%. From the results of the monitoring of pesticide residues in fruits and vegetables, fresh legume vegetables had the highest detection rate of 90.00%. Among the six major categories of pesticides monitored, fungicides in vegetables and fruits had the highest detection rates of 68.18% and 85.03%, respectively. The highest exceedance rate in vegetables was organophosphorus pesticides, accounting for 2.85%, while in fruits, neonicotinoid pesticides had the highest exceedance rate of 3.21%. From the perspective of sampling time, the peak detection rate of pesticide residues in fruits and vegetables in Wenzhou occurred in June and October. The index of food safety (IFS) of the 23 pesticides with a detection rate higher than 5% ranged from 0.000 7 to 0.694 2 based on the 95% monitoring value of pesticide residues, which were all less than 1. Calculated at maximum content, the IFS values of dithiocarbamate (calculated by CS2), chlorothalonil and propiconazole were all greater than 1, indicating that the maximum detection values of the three pesticides exceeded the acceptable safety risk. The risk level of acute dietary intake of the 23 pesticides ranged from 1.26% to 52.65%.ConclusionThe overall situation of pesticide residues in fruits and vegetables sold in Wenzhou from 2020 to 2023 is favourable, but the exceedance rate of pesticide in some fruits and vegetables is high. Special attention should be paid to the pesticide residues of fungicides, neonicotinoid insecticides and organophosphorus pesticides in fresh legume vegetables, bulb vegetables and some fruits sold in Wenzhou, such as acetamiprid in bayberry and cowpea, dimethomorph in strawberry, chlorpyrifos in leek, etc., and monitoring of pesticide residues in food need to be strengthened.